2019
DOI: 10.18805/ag.d-145
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Performance of Japanese Quail Hens (Coturnixcoturnix japonica) Fed with Feed Restriction Regimes during Growth Period

Abstract: Reproductive performance of quail hens (Coturnixcoturnix japonica) at sexual maturity was evaluated following two feeding restriction programs (100%, 90% and 80% of ad libitum) and energy metabolism (EM) of ration: 2900 Kcal/kg and 2800 Kcal/kg) between 2 weeks and 5 weeks of age with five replicates of 10 chicks per replicate. Body weight and feed conversion were measured weekly during feed restriction. After experimental feeding treatment, age at first egg, BW, egg weight, development of reproductive organ o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…In this study, the egg weight of the P1 group was greater than that of the P2 and P3 groups due to the higher protein content of the feed than that of the feed provided to the P0 group. is nding is consistent with the ndings of Hertamawati et al, (2019), which suggested that the higher the protein consumption, the greater the egg weight. Other factors that can in uence egg weight include environmental conditions, maintenance management, and most importantly, rations.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the egg weight of the P1 group was greater than that of the P2 and P3 groups due to the higher protein content of the feed than that of the feed provided to the P0 group. is nding is consistent with the ndings of Hertamawati et al, (2019), which suggested that the higher the protein consumption, the greater the egg weight. Other factors that can in uence egg weight include environmental conditions, maintenance management, and most importantly, rations.…”
Section: Discussionsupporting
confidence: 90%
“…Quail with treatment fermented Azolla 2.5% had the highest body weight at sexual maturity 179.75 g and the lowest was control 166.64 g. The result showed that given fermented Azolla on feed has significantly effect on increasing body weight at sexual maturity. Body weight at sexual maturity of quail around 167-187.67 g while the age of sexually was about 42.67-55.33 days [8]. Cross-breed kampung chickens fed a diet containing Azolla microphylla (10%, 15%, and 20%) gave higher body weight than control diets [9].…”
Section: Resultsmentioning
confidence: 98%
“…The weight of the first egg from quail fed with fermented Azolla meal up to 7.5% was bigger than control. The weight of first egg from quail was about 7.99-9.54 g [8]. The results showed that the egg weight was lower than the results from other study, weight of quail egg was around 11.32-11.80 g) [10], but have same result with another study, the average of quail egg weight is 8.40-8.92 g. Egg weight associated with the type of quail, feed nutrition, and age.…”
Section: Resultsmentioning
confidence: 99%
“…The consistent progress registered in bird nutrition is one of the key factors of recent development in the poultry industry (Sirsat et al, 2018). Most poultry nutrition research looks at protein, because the level of protein is the most important factor in the final cost of the compound feed Hertamawati et al, (2019) mention that protein and energy account for 85% of the final cost of compound feed). From the 20 amino acids that make up the protein structure, methionine and lysine levels are critically important in the composition of compound feed recipes for poultry growth (Melaku et al, 2019).…”
Section: Introductionmentioning
confidence: 99%